Analysis of Conditions and Problems of Pre-Departure Training for Caregiver Candidate Internships in Indonesia - Novita Rozaliana Fadillah, Andi; Fahrul Rochim, Julita (Riviera Publishing, 2023)
Within a decade, starting in 2008, the Japanese government opened up the acceptance of foreign workers in the caregiver field, and Indonesia is one of the countries with the most significant number of senders of caregivers in Japan. There are at least four routes for sending caregivers to Japan, one of which is through sending caregiver interns